Epistemic Emotions and Epistemic Cognition Predict Critical Thinking About Socio-Scientific Issues - Muis, Krista R.; Chevrier, Marianne; Denton, Courtney A.; Losenno, Kelsey M. (Frontiers in Education, 2021)
When thinking critically about socio-scientific issues, individuals’ expectations about the nature of knowledge and knowing, as well as their emotions when these expectations are met or not, may play an important role in critical thinking. In this study, we examined the role of epistemic emotions in mediating the effects of epistemic cognition on critical thinking when contending with conflicting information about genetically modified foods. Two hundred four university students completed a prior knowledge test on genetically modified foods, and then reported their epistemic beliefs about genetically modified foods. Participants then read a text that presented advantages and disadvantages of genetically modified foods, and reported the epistemic emotions they experienced during reading of that text. Participants then composed an argumentative essay about genetically modified foods, which were coded for critical thinking. Results from path analysis revealed that a belief in complex knowledge predicted less surprise and confusion, but more enjoyment. For the source of knowledge, a belief in the active construction of knowledge predicted less surprise and enjoyment. For justification for knowing, a belief that knowledge should be critically evaluated positively predicted curiosity, and negatively predicted confusion and boredom. Moreover, beliefs that knowledge about genetically modified foods is complex and uncertain positively predicted critical thinking. Confusion and anxiety also positively predicted critical thinking, whereas frustration negatively predicted critical thinking. Lastly, confusion mediated relations between epistemic beliefs and critical thinking. Results suggest complex relations between epistemic cognition, epistemic emotions, and critical thinking that have implications for educational practice as well as for future research on epistemic cognition and epistemic emotions.